The Malaysian wish stream : an illustrated history of Malaysian cadets at the Royal Military Academy Sandhurts - Lim, Johnny Eng Seng (Ibu Pejabat Tentera Malaysia, Kementerian Pertahanan Malaysia, 2002)
The Royal Military Academy Sandhurst has a worldwide reputation as the oldest and most famous institution of its type in the world. Many customs and traditions of this famous academy were adopted by Commenwealth Armies including Malaysia. It has also trained many royalties and national leaders including Yang DiPertuan Agong, His Majesty Tuanku Syed Sirajuddin Ibni Al-Marhum Tuanku Syed Putra Jamalullail.